Antifungal Activity of Ballota acetabulosa Against Yeast Candida and Cryptococcus Species - Dulger, Basaran; Ali Kilcik, Mehmet (Asian Journal of Chemistry, 2010)
The ethanol extracts prepared from the leaves, rootstock and the combined formulation of Ballota acetabulosa (L.) Benth. have been investigated for their antifungal activities against medical yeast Candida species (C. albicans ATCC 10231, C. tropicalis ATCC 13803 and C. guilliermondii ATCC 6260) and Cryptococcus species (C. neoformans ATCC 90112 and C. laurentii ATCC 34142) by the visual broth macrodilution method. All extracts exhibited a strong antifungal effect against the yeast cultures. The MIC values ranged from 3.12 to 25 mg/mL. Besides, extracts exhibited greater antifungal effect against Candida species than Cryptococcus species. It is therefore suggested that extracts could be used traditionally in the treatment of fungal infections especially against candidiasis.